2020
DOI: 10.1038/s41598-020-74427-9
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Botrytis cinerea by an anionic porphyrin: an alternative pest management of grapevine

Abstract: Botrytis cinerea is a necrotic plant fungus that causes gray mold disease in over 200 crops, including grapevine. Due to its genetic plasticity, this fungus presents strong resistance to many fungicides. Thus, new strategies against B. cinerea are urgently needed. In this context, antimicrobial photodynamic treatment (APDT) was considered. APDT involves the use of a photosensitizer that generates reactive oxygen species upon illumination with white light. Tetra-4-sulfonatophenyl porphyrin tetra-ammonium (TPPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…They also were able to show in a trial with grapevine clones (Chardonnay, Merlot, Sauvignon), that 12.5 µM TPPS has no adverse effect on grapevine roots. Botrytis cinerea on grapevine vs − 1.5 µM TPPS was shown to completely inhibit mycelial growth [28]. Gonzales et al [29] used 25 and 50 µM Methylene blue and 30 min sunlight illumination to treat petals and leaves of sweet orange plants infected with conidia of Colletotricum abscissum and were able to obtain a 3 log 10 reduction-and complete eradication of conidia in some samples.…”
Section: Resultsmentioning
confidence: 99%
“…They also were able to show in a trial with grapevine clones (Chardonnay, Merlot, Sauvignon), that 12.5 µM TPPS has no adverse effect on grapevine roots. Botrytis cinerea on grapevine vs − 1.5 µM TPPS was shown to completely inhibit mycelial growth [28]. Gonzales et al [29] used 25 and 50 µM Methylene blue and 30 min sunlight illumination to treat petals and leaves of sweet orange plants infected with conidia of Colletotricum abscissum and were able to obtain a 3 log 10 reduction-and complete eradication of conidia in some samples.…”
Section: Resultsmentioning
confidence: 99%
“…In the former category, we found that organoheterocyclic compounds, metabolites associated with nucleic acids, organic acids and carbohydrates, were all enriched in resistant individuals regardless of time. The metabolite superclass of organoheterocyclic compounds, including subclasses such as carbazole, porphyrin, and butanolide, are almost universally associated with anti-microbial or antioxidant activities [48][49][50]. Therefore, induction of these compounds by the onset of fungal colonisation within resistant individuals is likely to enhance defence against the pathogen.…”
Section: Melaleuca Disease Resistance Involves Mfs That Are Both Phen...mentioning
confidence: 99%
“…This therapy was also used successfully against phytopathogenic fungi such as Lasiodiplodia theobromae (causes vine trunk disease), Botrytis cinerea (causes plant necrosis), and Colletotrichum sp. (causes anthracnose in various fruit trees) [ 26 , 27 , 28 ]. As already mentioned, spores are crucial to spreading fungal diseases, and fungal conidia are relevant targets for photosensitization [ 29 ].…”
Section: Introductionmentioning
confidence: 99%